2020
DOI: 10.1177/0954407020924285
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic optimal energy management strategy considering battery health for hybrid electric bus

Abstract: The problem of battery health coupled with energy management brings a considerable challenge to the hybrid electric bus. To address this challenge, three contributions are made to realize optimal energy management control while prolonging battery life. First, a semi-empirical aging model of lithium iron phosphate battery is built and identified by the data fitting method, based on the battery cycling test. Besides, a severity factor map is constructed by employing the proposed aging model to characterize the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Based on our literature review, a gap in state of the art was identified: few articles [6,37,66,67] referred to the degradation of batteries from the point of view of electric vehicles user behavior. In most cases, articles only mentioned the point of view of Electrochemistry.…”
Section: Survey Shared Questionsmentioning
confidence: 99%
“…Based on our literature review, a gap in state of the art was identified: few articles [6,37,66,67] referred to the degradation of batteries from the point of view of electric vehicles user behavior. In most cases, articles only mentioned the point of view of Electrochemistry.…”
Section: Survey Shared Questionsmentioning
confidence: 99%
“…Compared with the rule-based control strategy, the fuel economy in this method improves by 16.73%. However, this method has high computational expenses so that the corresponding calculation speed is relatively slow [40]. Recently, Xie et al proposed a MPC method based on the optimal depth of discharge (DOD) of the battery.…”
Section: Introductionmentioning
confidence: 99%
“…The above advantages of performance modeling, or called column counting or Ahthroughput battery aging method, has made it become very popular in literatures related in Optimal EMS of HEV with battery aging consideration [52][53][54][55][56][57][58][59][60][61][62][63][64]. Lithium-ion battery LiFePO4 will be studied in this brief due to its advantages in safety, and longer life characteristic [65].…”
Section: Optimal Ems Of Hev With Battery Aging Considerationmentioning
confidence: 99%
“…The battery aging estimation model in Hu's work [57], Wu's work in [58], and Cui's work in [61], are directly estimating the damage of battery from the instantaneous Ah-throughput based on experimental data, then used the aging model in MPC as the EMS for HEV. Cai's work in [59] used the Ah-throughput model to indicate the battery health, and analyzed the impact of power split configuration on fuel consumption and battery capacity degradation in HEV city buses.…”
Section: Optimal Ems Of Hev With Battery Aging Considerationmentioning
confidence: 99%
See 1 more Smart Citation